Utveckling av tillbehör för handhållen maskin vid rengöring i cirkulära kanaler - Carmestedt, Anders; Östman, Erik (2012)
The work in this thesis is done with the methods learned in our education, Technical Design at the Luleå University of technology. The project took place in the town of Katrineholm and with the plumbing company PCT Systems AB. The method that is being used while cleaning pipes consists of a tool that is rotating by a wire connected to a power drill. When the tool is rotating in the pipe it cleans the inner wall, also known as milling. If the tool is stuck the power drill is twisted and the user loses their grip. With that there is a possibility that the user gets hurt. If the tool starts to lose momentum there is a risk that the wire is damaged. The result in this thesis is to remove these problems and to improve the usability of a power drill in work. The work was done with a part of the creative process that applies segregation of duties, with main function, part function and support functions. The main function in this thesis is a slip clutch and apart from that there are support functions that will ease the usability of the slip clutch. The final concept is a slip clutch that may be applied on a variety of power drills to be used in the cleaning and milling of pipes. The final product shall solve the problems that occur when a tool is stuck or struggling to maintain speed in the pipes. That way it will improve the work environment for the user. Validerat; 20120112 (anonymous)